A Case Study Of Jaring, Malaysia - Gabu, Almond Alson Mitty (2006)
This study is conducted with the objectives of identifying and recognizing Jaring's strengths and opportunities that Jaring could undertake in order to capture the target market effectively in terms of broadband services.